2017
DOI: 10.1038/s41598-017-14626-z
|View full text |Cite
|
Sign up to set email alerts
|

Nature of collective decision-making by simple yes/no decision units

Abstract: The study of collective decision-making spans various fields such as brain and behavioural sciences, economics, management sciences, and artificial intelligence. Despite these interdisciplinary applications, little is known regarding how a group of simple ‘yes/no’ units, such as neurons in the brain, can select the best option among multiple options. One prerequisite for achieving such correct choices by the brain is correct evaluation of relative option quality, which enables a collective decision maker to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Another possibility is that the optimal threshold distribution is different between the populations. Recently, it has been shown that the performance of collective decision by using only yes/no decision units is maximized when the threshold distribution of a collective decision-maker is matched with the distribution of the options' qualities [ 22 ]. This issue is worth examining in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the optimal threshold distribution is different between the populations. Recently, it has been shown that the performance of collective decision by using only yes/no decision units is maximized when the threshold distribution of a collective decision-maker is matched with the distribution of the options' qualities [ 22 ]. This issue is worth examining in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, biological research points toward the value of heterogeneity in behavioural thresholds for more accurate and resilient collective decisions [21,22]. For instance, a small proportion (3-12%) of Temnothorax workers are persistent in exploring during a nest-site decision [23], which may correspond to high acceptance threshold 'picky' ants who keep looking for the very highest quality nest sites.…”
Section: Relevance To Embodied Artificial Intelligencementioning
confidence: 99%
“…which response threshold distribution D h ) maximise the probability of success given a known number of options n and distribution of options' quality D q . Past experiments only considered Gaussian distributions of the options' qualities [9,35,24], however, environments with other distributions may exist. In our analysis, we consider three types of quality distributions D q ∈ {U, N , K}: the uniform distribution U(µ q , σ q ), the Gaussian distribution N (µ q , σ q ), and the bimodal distribution K(µ ′ q , µ ′′ q , σ ′ q , σ ′′ q ).…”
Section: Characterisation Of the Problemmentioning
confidence: 99%
“…Behaviours based on response thresholds have a reactive binary (yes/no) response determined by the stimulus intensity (or option quality) being above or below a threshold, and can be observed in several eusocial insect species [8,24,18,25,34,27]. Despite individuals' simplicity, systems composed of response threshold units can display accurate and rational collective behaviour [24,35,9,17], which is enabled by a crucial element of such systems, the heterogeneity of their individuals, each having a different threshold [18,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation